PlGF/FLT-1 deficiency leads to reduced STAT3-C/EBPβ signaling and aberrant polarization in decidual macrophages during early spontaneous abortion - Chang, Ruiqi; Dai, Jingcong; Wang, Li; Liu, Hao; Jiang, Huanhuan; Liu, Xiaoyu; Jiang, Linying; He, Fan; Hu, Lina (Frontiers in Immunology, 2023)
Introduction Dysregulated macrophage polarization (excessive M1-like or limited M2-like macrophages) in the early decidua contributes to allogeneic fetal rejection and thus early spontaneous abortion. However, the modulators of M1/M2 balance at the early maternal-fetal interface remain mostly unknown. Methods First-trimester decidual tissues were collected from normal pregnant women undergoing elective pregnancy terminations and patients with spontaneous abortion. We measured the expression of placental growth factor (PlGF) and Fms-like-tyrosine-kinase receptor 1 (FLT-1), and characterized the profiles of macrophages in decidua. Notably, we investigated the effect of recombinant human PlGF (rhPlGF) on decidual macrophages (dMφs) from normal pregnancy and revealed the underlying mechanisms both in vitro and in vivo. Results The downregulated expression of PlGF/ FLT-1 may result in spontaneous abortion by inducing the M1-like deviation of macrophages in human early decidua. Moreover, the CBA/J×DBA/2 abortion-prone mice displayed a lower FLT-1 expression in uterine macrophages than did CBA/J×BALB/c control pregnant mice. In in vitro models, rhPlGF treatment was found to drive the M2-like polarization of dMφs via the STAT3/CEBPB signaling pathway. These findings were further supported by a higher embryo resorption rate and uterine macrophage dysfunction in Pgf knockout mice, in addition to the reduced STAT3 transcription and C/EBPβ expression in uterine macrophages. Discussion PlGF plays a key role in early pregnancy maintenance by skewing dMφs toward an M2-like phenotype via the FLT-1-STAT3-C/EBPβ signaling pathway. Excitingly, our results highlight a rationale that PlGF is a promising target to prevent early spontaneous abortion.